Evaluation of narrow-band imaging signs in eosinophilic and lymphocytic esophagitis - Ichiya, Tamaki; Tanaka, Kyosuke; Rubio, Carlos A.; Hammar, Ulf; Schmidt, Peter T. (Endoscopy, 2017)
Background and study aims No specific endoscopic signs for diagnosing eosinophilic esophagitis (EoE) have been described and very few studies have reported endoscopic signs for lymphocytic esophagitis (LyE). This study aimed to assess the utility of narrow-band imaging magnifying endoscopy (NBI-ME) in predicting EoE/LyE diagnosis before histopathological assessment. Patients and methods Adult patients with dysphagia and/or food impaction who underwent esophagogastroduodenoscopy followed by NBI-ME and biopsies were included. Three previously reported NBI-ME signs were studied: beige mucosa, dot-shaped intra-epithelial papillary capillary loop (IPCL), and absent cyan vessels. These signs were compared with the histological diagnosis, and studied in patients with and without EoE or LyE. A predictive model containing the NBI-ME signs was analyzed, based on area under the curve (AUC). Results A total of 137 patients were enrolled. Based on histology 26 were diagnosed with EoE, 26 with LyE, and 85 were control patients with neither diagnosis. Significantly more EoE/LyE patients than control patients showed the NBI signs (P  < 0.001 for all three signs). Absent cyan vessels had the highest accuracy for differentiation (sensitivity 88 %, specificity 92 %). A combination of age, dot IPCLs, and absent cyan vessels was highly predictive of EoE/LyE, with an AUC of 0.952. Conclusions Three NBI-ME signs were found in the majority of patients with EoE/LyE and unlikely to be observed in controls. A combination of two NBI-ME signs and younger age had a higher degree of accuracy. This supports the claim that NBI-ME could be a reliable diagnostic modality for EoE/LyE predictors.